Aggression in Soccer Fan's: A Test of Akers' Social Learning Theory. Issue 12 (2nd December 2021) - Kabiri, Saeed; Masoomeh (Shamila) Shadmanfaat, Seyyedeh; Smith, Hayden; Cochran, John K.
ABSTRACT: Aggression involving sports fans has long been acknowledged, however it is only recently that researchers have applied criminological theory to gain a better understanding of the behavior. The current study employs Social Learning Theory as a means of understanding how deviant behavior is influenced by differential association, differential reinforcement, imitation, and definitions in the context of sports fans. Survey data from 372 soccer fans attending a stadium event in Iran was used to assess verbal and physical aggression. Structural Equation Modeling was utilized to model the direct and indirect effects of social learning theory. Findings indicate that marriage status (β = −.10, p =.05), age (β = −.11, p =.05), education (β = −.11, p =.05), differential associations (β =.24, p =.01), differential reinforcements (β =.21, p =.01), imitation (β =.17, p =.05), and definitions (β =.23, p =.01) have a direct effect on fans' aggressive behaviors. The model accounted for 44% of the variance in fans' aggression behaviors, 12% of the variance in differential reinforcements, 28% of the variance in definitions, and 16% of the variance in imitation. This indicates that fans who observe the aggressive behavior of others that they respect are more likely to engage in verbal or physical aggression. Policy implications include efforts by sports clubs to encourage and educate appropriate behavior patterns via the leaders of fan groups.